The Mekong is in transition, what does it mean for food security? - Downs, Shauna; Manohar, Swetha; Sok, Serey; Chhinh, Nyda; Fanzo, Jessica (2024)
Communities along the Mekong River are already seeing their food access shrink as the climate worsens. Smart imminent solutions could ease the burden.